Songhai Farm Initiative and Agricultural Development in Rivers State - Dagogo, Doctor Farah (Researchparks Publishing, 2022)
This work examines Songhai initiative farm and agricultural development in Rivers State. The Songhai farm, since its inception in Rivers State, has invested in a rural transformation strategy in agriculture which was referred to as green rural agro-revolution. It was a well-established agricultural initiative for training, production, processing, research and development centre for sustainable agriculture that takes a holistic approach to linking producers locally to meet consumers at home and abroad in market quantity. The Songhai initiative farm trades only in organic products and enforces its own internal standards for organic agriculture through its training programme and through its internal quality control system for the traceability of its products. However, this lofty agricultural initiative went into extinction due mainly to irrational conception of the benefits of such engagement. To address the issues herein, we employed the Rational Choice Theory so much espoused by Mancur Olison with its basic assumption that rational choice indicates that objectives, whether selfish or unselfish, should be pursued by means that are efficient and effective for achievable results. A sample size of 200 respondents was used for the study with a specific target on four (4) local government areas that share boundary with Bunu Tai, which is the location of the farm. Finding shows that if such farming initiative like Songhai farm were present before the discovery of oil, the culture of agriculture could not have been so relegated as it is today. In this regard the work recommended among others tings that Songhai initiative farm be sited in all the local government areas of Rivers State because of its benefits.